Association Between the Severity of Dysphagia and Various Parameters of the Cervical Spine; Videofluoroscopic Analysis in Neutral and Retraction Position of the Normal Volunteers. Issue 2 (15th January 2020) - Hong, Jae Taek; Oh, Joo Seon; Lee, Dong Hoon; Lim, Seong Hoon; Kim, Joon-Sung
Abstract : Study Design: Videoflurographic swallowing study in asymptomatic volunteers. Objective: The purpose of this study was to investigate the relationship between the severity of dysphagia and various parameters of the subjects. Summary of Background Data: Occipitocervical fixation is associated with several potential complications. Malalignment of craniovertebral junction and associated dysphagia have been well described in the literature. However, there has been little attention given to investigate the association between the degree of swallowing dysfunction and various patient's parameters. Methods: Thirty-nine healthy asymptomatic volunteers, 18 males and 21 females, were enrolled in this study. Based on videofluorographic swallowing study (VFSS), two scoring systems of swallowing dysfunction (dysphagia rating scale [DRS], dysphagia outcome and severity scale [DOSS]) were measured in neutral and retraction position. Multiple linear regression analysis was performed to evaluate the relationship between the degree of swallowing dysfunction and various factors of the subjects such as radiological and clinical parameters. Results: There was statistically significant correlation between DRS and DOSS ( r = −0.354, P < 0.05). Multiple regression analysis showed that there was a significant association of the dysphagia severity (DRS and DOSS) with the percentile change of the narrowest oropharyngeal diameter (OD) (%dn OD) ( r = 0.121, P < 0.01 and r = 0.020, P < 0.01, respectively). Percentile change of OD (neutral and retraction position) was positively associated with the difference of C0–2 angle ( r = 1.676, P < 0.01). None of the other variables such as age, sex, C0–1 angle, C1–2 angle, and C2–7 angle were significantly associated with the degree of dysphagia or %dn OD. Conclusion: This study demonstrated that the severity of dysphagia is significantly associated with the percentile change of OD and the C0–2 angle has considerable effect on the OD after O-C fusion. Therefore, C0–2 angle could be the most critical radiological parameter not only for predicting the stricture of oropharyngeal space but also for preventing postoperative dysphagia. Level of Evidence: 4 Abstract : We evaluated the relationship between the dysphagia severity and patient's parameters using videofluoroscopic study in neutral and retraction positionThere was a significant association of the dysphagia severity with the percentile change of the oropharyngeal diameter (OD) and the change of OD was positively associated with the difference of C0–2 angle.